Metodologi Tafsir Kontemporer dalam Buku Major Themes of the Quran Karya Fazlur Rahman - Abdurrohim (LPPI Universitas Al-Qolam Malang, 2020)
As the leading guide of Muslims in life and life, the Quran is always interesting to study, a lot of efforts of the scholars to interpret the contents of the holy verses in it. Fazlur Rahman is one of the many contemporary scholars who have the idea of a unique approach, and maybe it could be new in the world of interpretation. One approach in understanding the Koran, he poured in the book